Pentingnya Penguatan Pendidikan Karakter pada Anak Sekolah Dasar di Era Digital - Lisia Miranda (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The purpose of this research is to see and know how the importance of strengthening character education in elementary school children in the digital era. The research method used is Literature Study with SLR or Sytematic Literature Review method is to collect, analyze, and study from various research references related to the topic of discussion and from previous similar research results that have been conducted by others. Strengthening character education in elementary school children in the digital era is very important to be applied in various activities in children, especially during school subjects and other activities such as discipline, examples of some characters in folklore and so on which can become good habits so that children today can balance good character habits with the harmony of technological developments to improve the quality and quantity of individual human resources, especially in elementary school children who need a lot of knowledge for their future progress.